Comparative Evaluation of Demineralized Freeze-Dried Bone Allograft Combined with 0.75% Boric Acid Gel versus Demineralized Freeze-Dried Bone Allograft Alone in the Management of Subclass-B Furcation Defects - Prasanna Sawant; Pallavi Kamble; Nitin Gorwade; Sachin B. Mangalekar; Saumya Shankar; Shruti Kumbhare (Journal of Pharmacy and Bioallied Sciences, 2025)
Aim: This study aims to compare the efficacy of demineralized freeze-dried bone allograft (DFDBA) combined with 0.75% boric acid gel versus DFDBA alone in managing subclass-B furcation defects. Methods: A split-mouth clinical trial design was adopted, involving 20 sites with bilateral Grade B furcation defects in first or second mandibular molars. The control group received DFDBA treatment only, while the test group was treated with 0.75% boric acid gel in addition to DFDBA. Clinical parameters, including Plaque Index, Modified Gingival Index, Russell’s Periodontal Index, probing pocket depth (PPD), clinical attachment level (CAL), and relative attachment level (RAL), were measured at baseline, 3 months, and 6 months post-treatment. Bone fill from the furcation fornix to the base of the defect was evaluated radiographically at the same intervals. Results: Both treatment approaches demonstrated success in promoting bone regeneration. However, the addition of 0.75% boric acid gel did not significantly enhance bone fill compared to DFDBA alone. The primary determinant of bone regeneration was attributed to the intrinsic characteristics of DFDBA and the precision of clinical application, rather than the adjunctive effects of boric acid gel. Conclusion: While boric acid gel’s antibacterial and anti-inflammatory properties contributed to improved post-operative comfort, they did not result in measurable advantages in bone regeneration.